Financial Management as a System of Relations of the Enterprise for Highly Efficient Management of its Finances - Khominich, Irina P.; Rybyantseva, Mariya S.; Borodacheva, Lyubov V.; Dik, Elena V.; Afanasev, Evgenii V. (International Journal of Economics and Financial Issues, 2016)
At the current stage of development of Russia’s financial system, with quite high risks and interest rates, with only just gaining strength the stock market and the upcoming large-scale entering the domestic companies interest in the theory and practice of functioning of developed markets for financial instruments is obvious. Today, Finance of a business entity is an indicator of its competitiveness, indicator of its viability in a market economy. The complexity and diversity of internal and external financial relations of the enterprise determines the need for the effective management of its finances. Financial management of individual businesses was allocated in the countries with developed market economies in the early twentieth century in a special field of knowledge which is called “Financial management”. The effectiveness of each control system largely depends on its information systems. In conditions of transition to market economy the known formula “time - money” is supplemented with the similar formula: “the information - money”. With reference to financial management it acquires a direct sense. Keywords: financial management, management system, management finances, enterprise JEL Classifications: G02, G03, G32